Aarti performed after placing the goddess on the boat - Mumbai Archive Project Team (Jio Institute, 2024)
The boat owners consider it a great honour to receive the Goddess on their boat. Aaarti (waving the sacred fire in front of the deity) is performed when the Goddess arrives on deck, and blessings are taken from the scared fire of the aarti.